Implementasi Media Pembelajaran Google Classroom Pada Mata Pelajaran TIK Terhadap Motivasi Belajar Siswa Di SMPN 1 Cibingbin - Ainur Rafik; Sofhian Fajrin Nasrulloh (CV.ITTC INDONESIA, 2025)
This study aims to implement Google Classroom as a learning medium in Information and Communication Technology (ICT) subjects at SMPN 1 Cibingbin and to analyze its effect on students’ learning motivation. The background of this research is the low student motivation caused by conventional teaching methods that tend to be monotonous. The research employed a quantitative approach with a pre-experimental design, specifically the One Group Pretest-Posttest Design. The subjects were 30 eighth-grade students who were given a learning motivation questionnaire before (pretest) and after (posttest) the use of Google Classroom. Data analysis was conducted using the Wilcoxon Signed Rank Test and effect size calculation. The results showed a significant increase in students’ learning motivation, with the average score rising from 34.50 in the pretest to 40.17 in the posttest. The Wilcoxon test yielded Z = -3.633 with a significance value of 0.000 (<0.05), while the effect size r = 0.663 indicated a large effect. These findings prove that Google Classroom is effective in enhancing students’ motivation in learning ICT. Supporting factors include the availability of digital devices, school support, and teacher readiness, while inhibiting factors consist of limited internet connectivity and students’ varying abilities in operating the application.